Willingness of people who inject drugs to participate in a randomised controlled trial involving financial incentives to initiate hepatitis C treatment. (1st June 2022) - Marshall, Alison D.; Conway, Anna; Cunningham, Evan B.; Valerio, Heather; Silk, David; Alavi, Maryam; Wade, Alexandra; Lam, Thao; Zohrab, Krista; Dunlop, Adrian; Connelly, Chris; Christmass, Michael; et al.
Abstract: Background: Evidence regarding the acceptability of contingency management is limited. We investigated the willingness of people who inject drugs to participate in a randomised controlled trial (RCT) involving financial incentives to initiate HCV treatment. Methods: ETHOS Engage is an observational cohort study of people with a history of injecting drug use who either injected in the past six months or receive opioid agonist therapy (OAT) in Australia. We assessed willingness to participate in a RCT with financial incentives and factors associated with preference for entire incentive (60) at first clinic visit versus delayed incentive with logistic regression. Results: 93% (593/635) of eligible participants agreed to participate in an RCT with financial incentives of which 24% were Aboriginal or Torres Strait Islander, 84% had completed secondary school, and 59% injected drugs in the prior month. Willingness to participate in an RCT increased by amount offered: unspecified (72%), 20 (75%), 60 (80%), and 100 (85%). The preferred incentive distribution method over three clinical visits was entire incentive at first clinical visit (32%). Among those with a preferred distribution method (n = 369), factors associated with entire incentive at first clinic visit were being Aboriginal or Torres Strait Islander (aOR 1.75; 95% CI 1.05–2.94), completion of secondary school (aOR 0.46; 95% CI 0.26–0.83) and mainly injected heroin in month prior (aOR 1.82; 95% CI 1.03–3.20). Conclusion: Most participants were willing to participate in an RCT involving financial incentives to initiate treatment but differed regarding distribution. Study findings inform implementation of incentives in clinical practice. Highlights: Most participants were willing to participate in a randomised controlled trial with financial incentives. Willingness to participate in a randomised controlled trial increased by financial amount offered. The preferred method of incentive distribution over three clinical visits was receiving the entire incentive at first visit.